1995
DOI: 10.1016/0273-1177(95)00126-y
|View full text |Cite
|
Sign up to set email alerts
|

A review on the stability of liquid bridges

Abstract: Errors in theAlthough early studies dealing with the stability of liquid bridges were published long time ago, these studies were mainly concerned with the stability of axisymmetric liquid bridges between parallel, coaxial, equal-in-diameter solid disks, with regard to axisymmetric perturbations. Results including effects such as solid rotation of the liquid column, supporting disks of different diameters and an axial acceleration acting parallel to the liquid column can be found in several works published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…As previously stated, Qian et al 24 reported small drop sizes in a pressure-controlled deposition due to fast dynamics near the contact line. Here, achieving a fast-receding contact line is assisted by the withdrawal of the liquid near primary and satellite drops upon stability loss at the maximum-height stability limit 19 . Thus, the chain of drops arising upon breakup is the most stable (having the deepest potential well) state that is dynamically accessible to unstable bridges.…”
Section: Contact-angle Hysteresis Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated, Qian et al 24 reported small drop sizes in a pressure-controlled deposition due to fast dynamics near the contact line. Here, achieving a fast-receding contact line is assisted by the withdrawal of the liquid near primary and satellite drops upon stability loss at the maximum-height stability limit 19 . Thus, the chain of drops arising upon breakup is the most stable (having the deepest potential well) state that is dynamically accessible to unstable bridges.…”
Section: Contact-angle Hysteresis Effectmentioning
confidence: 99%
“…Quantifying liquid-bridge and jet breakup upon stability loss dates to the works of Plateau 15 and Rayleigh 16 , 17 . While early investigations of crystal growth and purification focused on determining the minimum liquid volume that can be held between circular discs 18,19 , the drop-size distribution following breakup is of prime interest in contact-drop dispensing and liquid-transfer applications [20][21][22] . Minimizing the dispensed-drop size relative to the needle diameter is central to surface patterning based on direct-write lithographic techniques 3,23 .…”
Section: Introductionmentioning
confidence: 99%
“…11 The impact of axial stretching on the stability of a liquid ligament has also a long history, 12,13 the lesson being that instability is suppressed as soon as the stretching rate overcomes the capillary instability rate based on the current ligament radius. 7,9,14,15 When formed by the rapid extension of a liquid bridge (a volume of liquid held by surface tension on supporting solid rods [16][17][18][19] ), the ligament linking the distant pulling supports thus breaks up at its extremities, 20 and does so first in the region close to the solid where stretching vanishes. 8,9,21 (This is almost always true: the breakup can occur in other places for low stretching speeds.)…”
mentioning
confidence: 99%
“…The stability of non-cynlidrical liquid bridges has been considered in several works 21,22 but the eigenmodes of oscillations have not been determined so far.…”
Section: Introductionmentioning
confidence: 99%